2020
DOI: 10.1098/rstb.2019.0112
|View full text |Cite
|
Sign up to set email alerts
|

Soil microbial community responses to climate extremes: resistance, resilience and transitions to alternative states

Abstract: A major challenge for advancing our understanding of the functional role of soil microbial communities is to link changes in their structure and function under climate change. To address this challenge requires new understanding of the mechanisms that underlie the capacity of soil microbial communities to resist and recover from climate extremes. Here, we synthesize emerging understanding of the intrinsic and extrinsic factors that influence the resistance and resilience of soil microbial communities to climat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
127
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 177 publications
(148 citation statements)
references
References 124 publications
3
127
0
2
Order By: Relevance
“… 2019 ). The resistance of microbial communities to disturbances is suggested to be linked to diversity (Bardgett and Caruso 2020 ) because diversity can increase the variability of species’ responses to environmental stress and may thus buffer essential ecosystem functions against environmental fluctuations (Naeem and Li 1997 ; Yachi and Loreau 1999 ). Under controlled conditions, Lori et al .…”
Section: Introductionmentioning
confidence: 99%
“… 2019 ). The resistance of microbial communities to disturbances is suggested to be linked to diversity (Bardgett and Caruso 2020 ) because diversity can increase the variability of species’ responses to environmental stress and may thus buffer essential ecosystem functions against environmental fluctuations (Naeem and Li 1997 ; Yachi and Loreau 1999 ). Under controlled conditions, Lori et al .…”
Section: Introductionmentioning
confidence: 99%
“…Following Oliver et al (2015), this capacity of ecosystems to deal with environmental stress (sometime referred to as overall resilience, see Hodgson et al (2015) and Mori (2016) for recent discussions on resilience terminologies) can be decomposed in the ecosystem resistance, that is the capacity to maintain its state during stress, and the recovery (also sometimes called 'engineering resilience'), which refers to the capacity to recover after the end of the stress (Hodgson et al, 2015;Oliver et al, 2015). Although soil microbes underpin carbon and nutrient cycling in ecosystems (Bender et al, 2016;Nannipieri et al, 2003), drivers of the microbial resistance and recovery are still poorly understood (Bardgett & Caruso, 2020;de Vries & Shade, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…This is potentially problematic, as it is assuming that rhizosphere processes, including contributions from mycorrhizal fungi, are not influencing the overall R S response. Previous studies have demonstrated the important role roots play in stabilising SOM (Hinsinger et al, 2009), with disturbed soils having a lower capacity to protect SOM due to mechanical disruption of macroaggregates, and hence C is more readily decomposed by microorganisms (Beare et al, 1994). Many, and potentially all, of the plant species at the site have associations with arbuscular mycorrhizae, which are known to increase SOM formation both directly as well as through their influence on soil aggregation (Rillig et al, 2001).…”
Section: Plant-induced Alteration To Soil Microhabitatmentioning
confidence: 99%